Customary land disputes in Indonesia - Sunarno; Khan, HannaAmbaras (Human Resource Management Academic Research Society, 2023)
In Indonesia, there is a dual system of governing customary land. It creates confusion when it comes to dispute resolution methods. Customary land disputes may lead to a bigger issue between disputants. The disputants might not get justice from the civil court due to the ownership issue of the land. This paper aims to study the existing national laws, customary laws, and dispute-resolution methods used in resolving customary land issues. This paper adopts a qualitative research method. Normative legal research is adopted to collect data from the legal materials, including primary, secondary, and tertiary materials. A socio-legal approach is adopted to ascertain and identify the experience in addressing and settling customary land disputes. A few short case studies are included to illustrate the issue of dispute resolution involving customary land. The findings show that the current method of resolving customary land dispute cause injustice, and distress and is ineffective to the indigenous people. Customary land disputes need to be resolved through amicable settlement or alternative dispute resolution (ADR) with a simple process that prioritizes the principles of kinship in the society or following indigenous or customary laws.